Starting and resourcing family and internal medicine residency programs as integral mission - Stephen P Merry; Bruce Dahlman; Adam P Sawatsky; Dennis Palmer; Kevin C Shannon; Thomas D Thacher (Health for All Nations, 2016)
Graduate medical education is an excellent means of building the capacity of health care systems in low and middle Income Countries (LMIC) and a growing way for physicians in the U.S to get involved in integral mission - the proclamation and demonstration of the Gospel. This white paper purposes to provide a "best practices" recommendations on family and internal medicine ("medical") residency program development in majority world settings. An expert panel of residency educators convened in November 2015 at the Global Missions Health Conference (GMHC) in Louisville, Kentucky and through an iterative process identified themes that were then further defined and clarified by medical residency faculty unable to be present. Participants largely agreed that integration and cooperation with the country's Ministry of Health (MOH) is essential for sustainable residency development. Recognition of family medicine as a specialty will enable graduates to succeed in the country's physician job market and health systems leadership. Recognition by the national church of the unique needs of their mission hospitals' educational programs to control their revenue in order to fund their programs' growth and development exemplifies the common wisdom to provide authority and resources where responsibility for good outcomes is expected. Co-training of general surgeons and medical residents who can provide essential surgical call coverage may lead to on-going synergies. Teaching by medical and surgical subspecialists is essential in medical residencies to provide the depth of instruction residents need to develop as excellent clinicians. Dependable scheduling of their specialty instruction allows residency program directors to assure inclusion of their content in the residency curriculum. In summary, participants agreed that teaching in medical residency programs in LMIC present excellent opportunities for national and expat Christian physician educators interested in integral mission.